ANALYSIS OF THE PLAGIARISM ISSUES IN SCIENTIFIC PUBLICATIONS AND RESEARCH OF COMPARISON METHOD BASED ON VARIABLE SIMILARITY - DYRIV, ANDRII; LOZYNSKA, OLGA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This publication offers an in-depth analysis of the issue of formula plagiarism, focusing specifically on variable similarity. We explore various approaches and methods for plagiarism analysis, concentrating on variable similarity detection, and assess their effectiveness in this context. By examining a range of scientific publications, we identify and classify diverse cases of formula plagiarism, taking into account variables and their similarity